Long-Lasting Effect of Infant Rats Endotoxemia on Heat Shock Protein 60 in the Pancreatic Acinar Cells: Involvement of Toll-Like Receptor 4 - Joanna Bonior; Jolanta Jaworek; Michalina Kot; Stanisław J. Konturek; Piotr Pierzchalski (Hindawi Limited, 2012)
Introduction. Lipopolysaccharide endotoxin (LPS) is responsible for septic shock and multiorgan failure, but pretreatment of rats with low doses of LPS reduced pancreatic acute damage. Aim. We investigated the effects of the endotoxemia induced in the early period of life on Toll-like receptor 4 (TLR4), heat shock protein 60 (HSP60) and proapoptotic Bax, caspase-9 and -3 or antiapoptotic Bcl-2 protein expression in the pancreatic acinar cells of adult animals. Material and Methods. Newborn rats (25 g) were injected with endotoxin (Escherichia coli) for 5 consecutive days. Two months later, pancreatic acinar cells were isolated from all groups of animals and subjected to caerulein stimulation (10−8 M). Protein expression was assessed employing Western blot. For detection of apoptosis we have employed DNA fragmentation ladder assay. Results. Preconditioning of newborn rats with LPS increased TLR4, Caspase-9 and -3 levels, but failed to affect basal expression of HSP60, Bax, and Bcl-2. Subsequent caerulein stimulation increased TLR4, Bcl-2, and caspases, but diminished HSP60 and Bax proteins in pancreatic acinar cells. Endotoxemia dose-dependently increased TLR4, Bax, HSP60, and both caspases protein signals in the pancreatic acini, further inhibiting antiapoptotic Bcl-2. Conclusions. Endotoxemia promoted the induction of HSP60 via TLR4 in the infant rats and participated in the LPS-dependent pancreatic tissue protection against acute damage.